2021
DOI: 10.1002/pat.5389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyetherimide sizing involving carbon nanotubes on interfacial performance of carbon fiber/polyetheretherketone composites

Abstract: The interaction between carbon fiber (CF) and thermoplastic resin presents weakened characteristic, which can be problematic of composites in structural applications. Therefore, it is of great significance to research techniques of CF surface modification to strengthen the interface of composites. Herein, based on the optimization of emulsion composition, polyetherimide (PEI) sizing involving carbon nanotubes (CNTs) was applied on CF surface to enhance the interface of CF/polyetheretherketone (PEEK) composites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…According to the mechanical measurements above, it could be concluded that the addition of ATP‐PEI‐CF steeply enhanced the hardness and modulus of UHMWPE than CF and PEI‐CF. Combined with the fracture surface of the composites above, there were a large number of resin whiskers in the interface of the fillers and the UHMWPE matrix in ATP‐PEI‐CF/UPE which caused by the increased chimeric sites due to the high rough surface of the ATP‐PEI‐CF hybrid 41 . The special interface structure improved the energy consumption of fiber destruction when the composite was subjected to force, thus enhancing the mechanical properties of the composite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the mechanical measurements above, it could be concluded that the addition of ATP‐PEI‐CF steeply enhanced the hardness and modulus of UHMWPE than CF and PEI‐CF. Combined with the fracture surface of the composites above, there were a large number of resin whiskers in the interface of the fillers and the UHMWPE matrix in ATP‐PEI‐CF/UPE which caused by the increased chimeric sites due to the high rough surface of the ATP‐PEI‐CF hybrid 41 . The special interface structure improved the energy consumption of fiber destruction when the composite was subjected to force, thus enhancing the mechanical properties of the composite.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7 shows the shore hardness, compressive modulus, and elastic strength of UHMWPE and its composites. As can be seen from 41 The special interface structure improved the energy consumption of fiber destruction when the composite was subjected to force, thus enhancing the mechanical properties of the composite.…”
Section: Mechanical Propertiesmentioning
confidence: 93%
“…[ 27 ] Relatively speaking, the sizing method is a simple, low‐cost and high‐efficiency modification method, so it has been widely used. [ 28,29 ]…”
Section: Introductionmentioning
confidence: 99%
“…[27] Relatively speaking, the sizing method is a simple, low-cost and high-efficiency modification method, so it has been widely used. [28,29] According to the principle of similarity compatibility, the sizing agent is generally selected to have a chemical structure similar to that of the matrix resin, which is similar in structure to give full play to the reinforcing effect of CF, thereby improving the interface bonding ability of CF/PEEK composites. Soluble polymers and monomers are used as sizing agents, in which epoxy sizing agents are the most widely used.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of these strategies is to improve the interfacial bonding strength between fibers and the matrix by providing more physical contact for mechanical interlocking, thereby creating rich active groups or good wettability for chemical bonding ( Karnati et al., 2020 ; Raphael et al., 2018 ; Sharma et al., 2014 ). Many methods for surface modification of CFs were proved to be effective, including sizing, coating ( Sepe et al., 2018 ; Nie et al., 2017 ; Su et al., 2021 ; Acar et al., 2020 ), chemical grafting ( Cheng et al., 2018a , 2018b ; Nasser et al., 2019 ; Banerjee et al., 2021 ; Krushnamurty et al., 2016 ; Jia et al., 2021 ), oxidation treatment ( Prakash and Rajadurai, 2017 ; Dai et al., 2011 ; Andideh and Esfandeh, 2016 ; Wang et al., 2019 ; Chukov et al., 2019 ; Sun et al., 2020 ), adding nanoparticles ( Lau et al., 2013 ; Yao et al., 2021 ; Liu et al., 2021 ; Kurtulus et al., 2021 ), etc. Unfortunately, strong acid or toxic polar organic reagent treatments are easy to cause defects on the fragile surface of CFs, sacrificing the inherent tensile strength of the CFs in some degree.…”
Section: Introductionmentioning
confidence: 99%